The poverty of theory & other essays - "Thompson, E.P." (London, 1978)
his classic collection of essays by E.P. Thompson, one of England$1 (Bs most renowned socialist voices, remains a staple text in the history of Marxist theory. The bulk of the book is dedicated to Thompson$1 (Bs famous polemic against Louis Althusser and what he considers the reductionism and authoritarianism of Althusserian structuralism. In lively and erudite prose, Thompson argues for a self-critical and unapologetically humanist Marxist tradition. Also included are three essays of considerable importance to the development of the New Left.s
Keywords: Socialism